Five-Minute Awake Snoring Test for Determining CPAP Pressures (Five-Minute CPAP Test): A Pilot Study. (11th January 2016) - Camacho, Macario; Ruoff, Chad M.; Kawai, Makoto; Modi, Rahul; Arbee, Jabri; Hekmat, Anahid; Robertson, Matthew; Zaghi, Soroush; Certal, Victor; Capasso, Robson; Kushida, Clete A.
Abstract : Objective . To develop a quick, simple, bedside test for determining continuous positive airway pressures (CPAP) for obstructive sleep apnea (OSA) patients. Study Design . Prospective case series at a tertiary medical center. Methods . The Five-Minute Awake Snoring Test for Determining CPAP (Five-Minute CPAP Test) was developed and tested. Patients wear a soft-gel nasal triangle mask while holding a tongue depressor with the wide section (1.75 cm) between the teeth. Fixed pressure nasal CPAP is applied while the patient simulates snoring at 4 centimeters of water pressure. The pressure is incrementally titrated up and then down to determine the lowest pressure at which the patient cannot snore (Quiet Pressure). Results . Overall, thirty-eight patients participated. All could simulate snoring. Correlation coefficients were statistically significant between Quiet Pressures and body mass index (r s = 0.60 [strong positive relationship], p = 0.0088 ), apnea-hypopnea index (r s = 0.49 [moderate positive relationship], p = 0.039 ), lowest oxygen saturation (r s = - 0.47 [moderate negative relationship], p = 0.048 ), and oxygen desaturation index (r s = 0.62 [strong positive relationship], p = 0.0057 ). Conclusion . This pilot study introduces a new concept, which is the final product of over one year of exploration, development, and testing. Five-Minute CPAP Test is a quick, inexpensive, and safe bedside test based on supine awake simulated snoring with nasal CPAP.